Patient-reported outcome measures can advance population health, but is access to instruments and use equitable? - McCabe, Carolyn F.; Wood, G. Craig; Franceschelli-Hosterman, Jennifer; Cochran, William J.; Savage, Jennifer S.; Bailey-Davis, Lisa (Frontiers in Pediatrics, 2022)
Patient reported outcome measures (PROM) can engage patients and clinicians to improve health outcomes. Their population health impact may be limited by systematic barriers inhibiting access to completion. In this analysis we evaluated the association between individual parent/child characteristics and clinic factors with parental completion of a locally developed PROM, the Early Healthy Lifestyles (EHL) questionnaire. Participants included parent-child dyads who presented at 14 pediatric clinics for regularly scheduled well-child visits (WCV) prior to age 26 months. EHL items include feeding practices, diet, play time, screen exposure, and sleep. Completion was categorized at patient- (i.e., parent-child dyad) and clinic-levels. Parents completed the 15-item EHL in the patient portal before arrival or in the clinic; ninety-three percent of EHL questionnaires were completed in the clinic versus 7% in the patient portal. High-completers completed EHL for half of WCVs; low-completers completed at least once; and non-completers never completed. Clinics were classified by EHL adoption level (% high completion): High-adoption: >50%; Moderate-adoption: 10-50%; and Low-adoption: <10%. Individual-level factors had negligible impact on EHL completion within moderate/low EHL adoption sites; high-adoption sites were used to evaluate infant and maternal factors in association with EHL completion using hierarchical logistic regression. Noncompletion of EHL was significantly associated (p<0.05) with infant use of public insurance (OR=1.92 [1.42, 2.59]), >1 clinic site for WCV (OR=1.83 [1.34, 2.50]), non-White birth mother (OR=1.78 [1.28, 2.47]), and body weight <2500 grams or gestational age <34 weeks (OR=1.74 [1.05, 2.90]). The number of WCVs, a proxy for clinic size, was evaluated but was not associated with completion. Findings indicate potential disparities between populations exposed to, completing, and benefitting from these tools.